"Feminine invasion" women and Philippine pharmacy in the early twentieth century - Nery, Leo Angelo (Philippine studies : historical and ethnographic viewpoints, 2018)
"Originally a male-exclusive profession in the nineteenth century. Philippine pharmacy became th domain of women in the early twentieth century. This sea change occurred as educational institutions began to cater to women's career aspiration in pharmacy and especially after the US colonial school system introduced domestic science as a mandatory subject for girls, many of whom prsued pharmacy education in college. Women pharmacists set up retail drugstores in or near their residences, indicating pharmacy's compatibility with women's home-based roles. A contribution to gender history, this article shows that women actively challenged extant gender boundaries, which helped dismantle make exclusivity in other fields."